(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Fragile X Syndrome (FXS) is the most common known inherited form of intellectual disability (ID), caused by a CGG repeat expansion of the FMR1 gene. The aimed of the study was to screen FMR1 mutation among the ID population followed by cascade testing in a remote area. A PCR-based method was used to screen FMR1 expanded alleles using dried blood spot cards in Flores Island, one of the very remote areas in East Indonesia. The screening included 130 males and 81 females from three schools of children with ID. The screening identified three individuals with expanded alleles including two full mutation males and one premutation male. No expanded allele was detected in females. A second blood sample for confirmatory diagnosis was done using Southern blot. Cascade testing in a remote area of Indonesia found a multigenerational family with a large number of cases with FXS. FXS screening of ID populations followed by cascade testing in positive FXS family in a remote area with challenging accessibility is recommended.